The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.48550/arxiv.2107.05098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An elementary approach to the homological properties of constant-rank operators

Abstract: Using properties of the alternating algebra, we give a surprisingly simple and constructive proof of Rait , ȃ's result that every constant-rank operator A possesses an exact potential B and an exact annihilator Q. Our construction is completely self-contained and improves on the order of both the operators constructed by Rait , ȃ and the explicit formula for annihilators of elliptic operators due to Van Schaftingen. We also prove a generalized Poincaré lemma for a class of mean-value zero Schwartz functions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In this vein, Schulenberger and Wilcox [17,18] introduced the constant-rank condition (5) ∀ξ ∈ R N − {0}, rank A(ξ) = const., which they proved to be a sufficient condition for the validity of the fullspace coercive estimate (4) when p = 2 (in which case (3) is equivalent to (4)). Inspired by the estimates of Schulenberger and Wilcox, Kato [13] and Murat [14] proved that the constant-rank property further implies that the canonical linear L 2 -projection T 2 : L 2 (Ω; V ) → N 2 (A, Ω) extends to an L p -bounded projection in the sense that…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, Schulenberger and Wilcox [17,18] introduced the constant-rank condition (5) ∀ξ ∈ R N − {0}, rank A(ξ) = const., which they proved to be a sufficient condition for the validity of the fullspace coercive estimate (4) when p = 2 (in which case (3) is equivalent to (4)). Inspired by the estimates of Schulenberger and Wilcox, Kato [13] and Murat [14] proved that the constant-rank property further implies that the canonical linear L 2 -projection T 2 : L 2 (Ω; V ) → N 2 (A, Ω) extends to an L p -bounded projection in the sense that…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…To work out the case when A is not a maximal-rank operator, we require to briefly discuss the dichotomy between constant-rank operators and elliptic complexes. Recently, Raita [16] (see also the simplified proof given in [5]) showed that there exists a surjective correspondence between elliptic complexes and constant-rank operators. There, the author proved that if A satisfies the constant rank property, then there exists a differential complex…”
Section: 7mentioning
confidence: 99%
“…Following the works of Wilcox & Schulenberger [20] and Murat [17] (also see Fonseca & Müller [9]), operators A or B of the form (1.3) are said to be of constant rank (over R) provided dim R (A[ξ](V )) or dim R (B[ξ](W )), respectively, are independent of the phase space variable ξ ∈ R n \{0}. By Raita [18] (also see [3]), every constant rank operator possesses a constant rank potential.…”
mentioning
confidence: 99%